Faktor – Faktor Yang Mempengaruhi Kejadian Penyakit Demam Berdarah Dengue (DBD) Dan Jenis Serotipe Virus Dengue Di Kabupaten Semarang - Sucipto, Pramudiyo Teguh; Raharjo, Mursid; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2015)
Background: Dengue infection continues to present a seriuos public health problem.The cases of Dengue Haemorrhagic Fever (DHF) in Semarang District has increased significantly and cause death. The purpose of this study was to determine the factors that affect the incedence of dengue and dengue virus serotype in Semarang Distric.Method : This is case control study using 54 cases and 54 control are people who live around the case with the caracteristics of age one the same with case and sex of the case.The analysis methods applied were univariate and bivariates with chi-squre and multivariate with logistic regression. Results : Risk factors incidence of dengue in Semarang District were humidity in the room (OR = 5.8; 95% CI = 1.322 to 14.170), the eksistence larvae in the water container (OR = 6.6; 95% CI = 2.386 - 18.277), the habit of using anti-mosquito / repellent (OR = 4.4; 95% CI = 1.076 to 8.875), the habit of hanging clothes (OR = 3.9; 95% CI = 1018 to 9.861). Serotype of dengue virus dominant Den-1.Conclusion : The factors that influence the incidence of DHF are the eksistence larvae the water container, the habit of using anti-mosquito / repellent, the habit of hanging clothes and humidity in the room. Serotype of dengue virus dominant is Den-1. Suggestion necessary environmental management by changing physical environment and the DHF program vector Aedes aegypti intervention. Keywords : Dengue Haemorragic Fever, Serotype of dengue virus